MAKING MANAGEMENT DECISIONS TO OVERCOME UNCERTAINTY: AN ETHICAL PERSPECTIVE - SHUBA, Tetiana; LIASHEVSKA, Viktoriia; GLIEBOVA, Natalia; KOZARENKO, Lyubov; POPOVYCH, Arsenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article defines the role of the ethical aspect in the process of making managerial decisions. The principles that should be followed in the process of making managerial decisions are defined. The advantages of forming a sense of trust on the part of stakeholders to the company are characterised.The real way out of the situation with the problems of ensuring the normal operation of the enterprise in the present and future is based on mastering the methodologies and methods of making managerial decisions. This problem is particularly acute in the context of production instability and recession. In addition, economic decisions are growing rapidly. The very existence of a company often depends on how economically sound decisions are made.Socio-economic processes, their instability and uncertainty, and the dynamism of production lead to a sharp increase in the number of difficult economic situations. The solution and forecasting of which is almost impossible without the use of special economic and mathematical methods and techniques.In today's changing and unpredictable business environment, uncertainty is an inevitable reality for organisations of all sizes and industries. Economic downturns, natural disasters, market disruptions and technological innovations are just a few examples of factors that can create uncertainty and disrupt business operations. However, successful companies have learnt to navigate these uncertain times and even thrive in the face of adverse circumstances.Overcoming uncertainty requires a proactive and strategic approach. Successful companies must anticipate and prepare for potential disruptions, and be flexible enough to respond quickly to unforeseen events. While no two businesses are alike, there are some common strategies that successful companies use to manage uncertainty. By understanding and implementing these strategies, organisations can not only survive, but thrive in the face of uncertainty.
Keywords: social responsibility; management decisions; uncertainty; organisational structure; entrepreneurship